2017
DOI: 10.1093/ijnp/pyx056
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine System Dysregulation in Major Depressive Disorders

Abstract: Anhedonia is considered a core feature of major depressive disorder, and the dopamine system plays a pivotal role in the hedonic deficits described in this disorder. Dopaminergic activity is complex and under the regulation of multiple brain structures, including the ventral subiculum of the hippocampus and the basolateral amygdala. Whereas basic and clinical studies demonstrate deficits of the dopaminergic system in depression, the origin of these deficits likely lies in dysregulation of its regulatory affere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
358
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(376 citation statements)
references
References 156 publications
(174 reference statements)
12
358
1
5
Order By: Relevance
“…Inhibition in activity at the DA receptor in the striatal region via a decrease in the concentrations of calcium and sodium channels at the presynaptic ending results in a significant decrease in locomotor activity (60). Thus, DA has been determined to play a vital role during the pathogenesis of depression (61). Along with DA, 5-HT has also been suggested as an important neurotransmitter that is involved in the pathogenesis of major depressive disorders (55).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition in activity at the DA receptor in the striatal region via a decrease in the concentrations of calcium and sodium channels at the presynaptic ending results in a significant decrease in locomotor activity (60). Thus, DA has been determined to play a vital role during the pathogenesis of depression (61). Along with DA, 5-HT has also been suggested as an important neurotransmitter that is involved in the pathogenesis of major depressive disorders (55).…”
Section: Discussionmentioning
confidence: 99%
“…The GABA and glutamate systems, the primary inhibitory and excitatory transmitters in the brain, have been shown to be altered in MDD (Godfrey et al, 2018;Voineskos et al, 2019). As well as this, neuromodulators such as serotonin and dopamine, which influence neural excitability, are known to be affected in MDD (Belujon and Grace, 2017;Morrissette and Stahl, 2014) and to play a role in cortical activity changes between EC and EO conditions (Wan et al, 2019). It thus seems possible that the reported changes in cortical dynamic reactivity are related to changes in these systems (Hu et al, 2019;Ramirez-Mahaluf et al, 2017;Wiebking et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In recent years, however, basic and clinical studies have demonstrated that DA is also involved in the pathogenesis of depression. 28 As is well known, the delivery process of typical neurotransmitters roughly includes the following steps: docking of synaptic vesicles on the presynaptic membrane, fusion of synaptic vesicles with the presynaptic membrane, the release of neurotransmitters and the clearance of neurotransmitters. 29 Abnormal adjustment of any one of these steps will impede the transmission of neurotransmitters.…”
Section: F I G U R Ementioning
confidence: 99%